Impact of Fast Track Clinical Practice Guideline on Surgical Waiting Time and Blood Transfusion in Ectopic Pregnancy: A Quasi-Experimental Study in a Tertiary Hospital - Sanguanchua, Sunittha; Wongmuneeworn, Wanida; Sriruang, Ampan (Journal of Health Science of Thailand, 2024)
This quasi-experimental study aimed to compare surgical waiting time and blood transfusion in ectopic pregnancy patients before and after implementing the Fast Track Clinical Practice Guideline (CPG) at Hatyai tertiary hospital. The study involved 136 women diagnosed with ectopic pregnancy, confirmed through clinical signs, ultrasound findings, and pathology, between January 2023 and July 2024. The CPG, implemented in October 2023, applied lean principles to standardize preoperative protocols and reduce waiting times. Surgical waiting times and blood transfusion rates before and after CPG were analyzed with Wilcoxon Rank Sum test, and Fisher’s exact test or Chi square test as appropriated,with significance at p<0.05. The implementation of the Ectopic Fast Track CPG significantly reduced median surgical waiting time from 97 minutes to 55 minutes (p<0.05). Although the reduction in median blood loss from 500 mL to 425 mL in the post-CPG group was not statistically significant, it influenced significantly lower requirement for postoperative blood transfusion from 55.6% to 37.5%. Overall, the amount of blood loss did not contribute to severe complications such as hemorrhagic shock (11.8% vs 8.1%) or acute renal failure (1.4% vs 3.1%). Overall, the Fast Track CPG effectively shortened waiting times and reduced the need for blood transfusions in ectopic pregnancy surgeries.